THE CORRELATION OF ENGLISH SCORE IN NATIONAL EXAMINATION FOR STUDENTS WITH ENGLISH ACHIEVEMENT AND ITS IMPACT AS A PREDICTION TOOL - Nursiati, Nursiati; Sudarsono, Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to find out the correlation of English score in National Examination for Junior High School students with English achievement in 1st semester and its impact as a prediction tool. This research showed that 8.67% English score in National Examination has no impact to students' English achievement in the 1st semester of High School, 34.78% of English score in National Examination has low impact, 39.13% has moderate impact, and 13.04% of English score has substantial impact toward students' achievement. Therefore, it can be said that only 13.04% of all scores have strong influence toward students' achievement in High School, especially in 1st semester.Â Keywords: English score, National Examination, English achievement